Introduction - Thomas, Mandy (1998)
This introduction to the volume places the study of migration within the wider processes of social change and the complex actions of class, gender and ethnicity that are integrated into the experience of displacement. It argues that the articles in this volume contribute important new ethnographic and theoretical analyses to our knowledge and understanding of the constraints and the opportunities provided by cultural diversity in several societies by elaborating upon recent advances made in conceptualisations of migrancy. It places particular emphasis on developing phenomenological approaches to migration studies which incorporate the lived experience of migrants into any analysis. It also suggests that redressing the neglect of this area of study in Australia has the possibility of generating informed interruptions into the current political shift towards divisive public debates on immigration and cultural pluralism.